2018
DOI: 10.1111/eci.12996
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic AMPK and energy balance

Abstract: AMP‐activated protein kinase (AMPK) is the main cellular energy sensor. Activated following a depletion of cellular energy stores, AMPK will restore the energy homoeostasis by increasing energy production and limiting energy waste. At a central level, the AMPK pathway will integrate peripheral signals (mostly hormones and metabolites) through neuronal networks. Hypothalamic AMPK is directly implicated in feeding behaviour, brown adipose tissue (BAT) thermogenesis and browning of white adipose tissue (WAT). It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
64
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 147 publications
(416 reference statements)
2
64
0
2
Order By: Relevance
“…These findings seem paradoxical based on previous findings indicating that serotonin in the central nervous system increases BAT thermogenesis [31][32][33][34] . These opposing functions of central and peripheral serotonin are consistent with findings from other highly conserved regulators of energy balance such as the AMP-activated protein kinase where genetic reductions of hypothalamic AMPK increases energy expenditure 35 , while reductions of AMPK in adipose tissue lower energy expenditure and iWAT browning 36 . A similar paradigm of opposing functions between central and adipose specific mTOR has also been observed [37][38][39] .…”
Section: Discussionsupporting
confidence: 82%
“…These findings seem paradoxical based on previous findings indicating that serotonin in the central nervous system increases BAT thermogenesis [31][32][33][34] . These opposing functions of central and peripheral serotonin are consistent with findings from other highly conserved regulators of energy balance such as the AMP-activated protein kinase where genetic reductions of hypothalamic AMPK increases energy expenditure 35 , while reductions of AMPK in adipose tissue lower energy expenditure and iWAT browning 36 . A similar paradigm of opposing functions between central and adipose specific mTOR has also been observed [37][38][39] .…”
Section: Discussionsupporting
confidence: 82%
“…It has been reported that in POMC or AgRP neurons, the specific knockout of AMPK results in the destruction of energy balance, and the inhibition of AMPK in the hypothalamus lowers HGP and blood glucose in diabetes and obesity, 40 emphasizing that hypothalamic AMPK is an important integrator for controlling energy metabolism. However, it is important to note that contrary to peripheral AMPK, the activation of hypothalamic AMPK can increase HGP and hepatic IR in obese individuals 49 . As expected, we observed that IR and HFD increased hypothalamic AMPK phosphorylation (Thr172) in SH‐SY5Y cells or rats, whereas MBH JAZF1 resulted in the inhibition of hypothalamic AMPK phosphorylation (Thr172).…”
Section: Discussionsupporting
confidence: 77%
“…A second mechanism proposed for nicotine-induced weight loss and increased thermogenesis in rodents and humans is by inactivation of the hypothalamic AMP-activated protein kinase (AMPK)/BAT axis. This is a pathway in which reduced AMPK levels in the ventromedial nucleus of the hypothalamus activate the SNS to stimulate BAT thermogenesis (132). Nicotine also induces an increase in anorexic signaling in the hypothalamus, decreasing hunger and feeding, and an increase in physical activity and substrate oxidation, leading to increased NST (132)(133)(134).…”
Section: Sympathomimeticsmentioning
confidence: 99%
“…This is a pathway in which reduced AMPK levels in the ventromedial nucleus of the hypothalamus activate the SNS to stimulate BAT thermogenesis (132). Nicotine also induces an increase in anorexic signaling in the hypothalamus, decreasing hunger and feeding, and an increase in physical activity and substrate oxidation, leading to increased NST (132)(133)(134). Nicotine and liraglutide, a glucagon-like peptide 1 (GLP-1) receptor agonist, promote body weight reduction via increasing satiety and mediating BAT thermogenesis through the hypothalamic AMPK axis (131, 134 -136).…”
Section: Sympathomimeticsmentioning
confidence: 99%